Comparison of Adverse Kidney Outcomes With Empagliflozin and Linagliptin Use in Patients With Type 2 Diabetic Patients in a Real-World Setting - Lee, Yueh-Ting; Hsu, Chien-Ning; Fu, Chung-Ming; Wang, Shih-Wei; Huang, Chiang-Chi; Li, Lung-Chih (Frontiers in Pharmacology, 2021)
Background: To compare the effects of empagliflozin and linagliptin use on kidney outcomes of type 2 diabetes mellitus (T2DM) patients in a real-world setting. Methods: The study involved a propensity score-matched cohort comprising new users of empagliflozin or linagliptin with T2DM between January 1, 2013 and December 31, 2018 from a large healthcare delivery system in Taiwan. Clinical outcomes assessed: acute kidney injury (AKI), post-AKI dialysis, and mortality. Cox proportional hazard model was used to estimate the relative risk of empagliflozin or linagliptin use; a linear mixed model was used to compare the average change in estimated glomerular filtration rate (eGFR) over time. Results: Of the 7042 individuals, 67 of 3521 (1.9%) in the empagliflozin group and 144 of 3521 (4.1%) in the linagliptin group developed AKI during the 2-year follow-up. Patients in the empagliflozin group were at a 40% lower risk of developing AKI compared to those in the linagliptin group (p =0.001). Stratified analysis showed that empagliflozin users ≥ 65 years of age, or with a baseline eGFR < 60 mL/min/1.73 m2, or with a baseline glycohemoglobin ≦ 7% experienced attenuated benefits with respect to AKI risk. A smaller decline in eGFR was observed in empagliflozin users compared to linagliptin users regardless of AKI occurrence. Conclusions: Empagliflozin users were at a lower risk of developing AKI and exhibited a smaller eGFR decline than linagliptin users. Thus, empagliflozin may be a safer alternative to linagliptin for T2DM patients.